Seleção de fêmeas de pacu para indução hormonal: Efeito da idade e dos métodos de avaliação - Schorer, Marianne; Moreira, Renata Guimarães; Batlouni, Sergio Ricardo [UNESP] (Boletim do Instituto de Pesca, 2016)
In this study, we investigated the reproductive cycle and spawning season of old (OFs) and young (YFs) P. mesopotamicus females, aiming to improve the process of selection of suitable fish for induced spawning. We also evaluated the accuracy of using external body characteristics in selecting suitable females. To that, 60 OFs and 60 YFs (10 and four years old, respectively) were submitted to seven samplings during two reproductive cycles. In each sampling, females (five to 10 per treatment) were randomly chosen to evaluation of plasma concentrations of gonadal steroids and ovary composition (biopsies and stereology). Females were also submitted to an external evaluation concerning the length of abdominal thickness, the degree of the abdominal rigidity and the aspect of urogenital papilla. In spite of OFs have shown reduced concentrations of 17α-hydroxyprogesterone during the spawning season, we observed that OFs and YFs kept in captivity had similar reproductive cycles and spawning seasons (in December for both groups). We do not recommend the exclusive use of external evaluation for selecting breeders to spawning induction due to a great inaccuracy of data and lack of association with histology and ovarian biopsy, which are more accurate and reliable.
Selection of pacu females to hormonal induction: Effect of age and of evaluation methods
Keywords: Breeder selection; Induced spawning; Ovarian biopsies; Reproductive cycle; Unsuccessful ovulation